2007
DOI: 10.1002/bip.20884
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Zein secondary structure in solution by circular dichroism

Abstract: The proline-rich N-terminal domain of gamma-zein has been reported in relevant processes, which include its ability to cross the cell membranes. Evidences indicate that synthetic hexapeptide (PPPVHL), naturally found in N-terminal portion of gamma-zein, can adopt the polyproline II (PPII) conformation in aqueous solution. The secondary structure of gamma-zein in maize protein bodies had been analyzed by solid state Fourier transform infrared and nuclear magnetic resonance spectroscopies. However, it was not po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Analysis of the secondary structure of the entire ␥-zein protein by CD spectra in aqueous media showed that the whole protein has a high helical content but a low PPII conformation content, at 55 and 7%, respectively (57). In contrast, the synthetic peptide (PPPVHL) 8 , corresponding to the repeat region, has been shown to adopt an amphipathic polyproline II conformation (27,44) and has been linked to a new family of cell-penetrating peptides (58).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the secondary structure of the entire ␥-zein protein by CD spectra in aqueous media showed that the whole protein has a high helical content but a low PPII conformation content, at 55 and 7%, respectively (57). In contrast, the synthetic peptide (PPPVHL) 8 , corresponding to the repeat region, has been shown to adopt an amphipathic polyproline II conformation (27,44) and has been linked to a new family of cell-penetrating peptides (58).…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Owing to its semiextended nature, the P II protein domains are predictably highly solvent exposed in aqueous media. 22 Although amphipathic P II -forming sequences do appear in nature, 23,24 there is no evidence for the existence of a natural P II helix that would be purely hydrophobic.…”
Section: Hydrophobic Peptidesmentioning
confidence: 99%
“…Zein is the major storage protein of corn and an important source of protein in the human diet either through direct consumption or through consumption of animals whose feed is based on corn, such as poultry or swines [13]. Although zein is known since 1821 [1415], there is only recent interest in this protein focusing on its potential technological use [1617].…”
Section: Introductionmentioning
confidence: 99%